ASSESSMENT AND ANALYSIS OF THE PHYSICAL VULNERABILITY OF ABPAKHSH CITY AGAINST SEISMIC HAZARDS - Mohsen POURKHOSRAVANI; Somayeh Sadat SHAHZEIDI; Tayebeh MAHMOUDI MOHAMMAD ABADI (European Journal of Geography)
The natural hazards, especially the earthquake, cause serious damage to skeletal and physical infrastructure as well as to human communities in cities. Therefore, assessing the vulnerability f cities against these hazards will have a significant impact in reducing the damage caused by these hazards. Therefore, this study assessed the physical vulnerability of Abpakhsh city to seismic hazard using Dematel, AHP and GIS models. The results show that, according to the AHP model, seismicity and earthquake strength parameters were 0.259 and 0.251, respectively, for the seismicity index and seismic parameters and materials for physical vulnerability with the highest rank of 0.35 and 022, respectively. In the Dematel method, the fault seismic power parameter and the severity of the earthquake with J- R is as follows: (0.086 and 0.063) for the seismic sub-index and seismicity and building materials are as follows with J-R, respectively: (0.070 and 0.055) for physical vulnerability, the most influential maternal agents and soil depths with J + R (0.110) and slope with J + R (0.103) for seismicity and building materials with J + R (0.085) and seismicity With J + R (0.079) for Physical Vulnerability. These factorsare the most interconnected parameters in terms of seismicity and physical vulnerability of Abpakhsh city. In general, the results show that as the northwest of the city progresses, the amount of seismicity and damage will increase.